Sustainable Tourism Development In Tangerang City: How To Build A Community-Based Ecotourism Concept - Rd. Hera Merdeka Khazinatul Khaeriah (Institute of Computer Science (IOCS), 2021)
Ecotourism is a form of travel to natural areas that is carried out with the aim of conserving the environment and preserving the life and welfare of the local population, ecotourism is carried out in order to keep tourist areas intact and sustainable, in addition to maintaining the culture and welfare of the community. hope to be able to maintain the sustainability of ecological processes that continue to support living systems as well as protect biodiversity and support the local community in order to be able to maintain local culture and at the same time improve their welfare. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that ecotourism-based tourism in Keranggan Village can be seen in the potential of Keranggan Village which has two aspects of tourism resources, namely natural resources and cultural resources. Natural resources include the diversity of flora and fauna in the area, while cultural resources include livelihoods, religious systems, kinship systems and scattered arts. These resources can be used as tourist attractions, while the management activities of the Keranggan tourist village are aimed at realizing the Keranggan Village as a community-based ecotourism village with the support of partners from the Keranggan Village Government and the establishment of the Cipta Boga Cooperative which is able to organize all tourism empowerment programs in the Kampung area. Keranggan ecotourism.